A cluster randomised controlled trial of a web-based youth mental health service in Australian schools - Bridianne O'Dea; Mirjana Subotic-Kerry; Catherine King; Andrew J. Mackinnon; Melinda R. Achilles; Melissa Anderson; Belinda Parker; Aliza Werner-Seidler; Michelle Torok; Nicole Cockayne; Simon T.E. Baker; Helen Christensen (Elsevier, 2021)
Background: Secondary schools have attempted to address gaps in help-seeking for mental health problems with little success. This trial evaluated the effectiveness of a universal web-based service (Smooth Sailing) for improving help-seeking intentions for mental health problems and other related outcomes among students. Methods: A cluster randomised controlled trial was conducted to evaluate the 12-week outcomes of the Smooth Sailing service among 1841 students from 22 secondary schools in New South Wales, Australia. Assignment was conducted at the school level. The control condition received school-as-usual. The primary outcome was help-seeking intentions for general mental health problems at 12-weeks post-baseline. Secondary outcomes included help-seeking behaviour, anxiety and depressive symptoms, psychological distress, psychological barriers to help-seeking, and mental health literacy. Data were analysed using mixed linear models. This trial was registered with the Australian and New Zealand Clinical Trials Registry (ACTRN12618001539224). Findings: At 12-weeks post-baseline, there was a marginal statistical difference in the relative means of help-seeking intentions (effect size=0•10, 95%CI: -0•02-0•21) that favoured the intervention condition. Help-seeking from adults declined in both conditions. There was a greater reduction in the number of students who "needed support for their mental health but were not seeking help" in the intervention condition (OR: 2•08, 95%CI: 1•72-2.27, P<•0001). No other universal effects were found. Participants found the service easy to use and understand; However, low motivation, time, forgetfulness, and lack of perceived need were barriers to use. Interpretation: Smooth Sailing led to small improvements in help-seeking intentions. Refinements are needed to improve its effectiveness on other mental health outcomes and to increase student uptake and engagement. Funding: HSBC and Graf Foundation.